The Redesigning Icons to Reduce User Confusion - Kleddao Satcharoen; Boonyawat Bunyanuson; Panassava Siripreechawat; Pikulkaew Tangtisanon (My University, 2023)
Abstract Redesigning icons to reduce user confusion was created to solve the problems of Icons that are modelled on objects that are not popular for nowadays or are confusing to convey the meaning to the user to gain more effectively, increased accuracy and convenience for the user. A new icon design project to reduce user confusion. It arises from researching design-related information such as Affordance theory, image processing, color and mood theory, or even in terms of pixel size Which affects the use. Bring knowledge to design icons to better solve problems and respond to the needs of the user. This was done by collecting user data through questionnaires on the website with random questions and options. To take into account the performance of icons that are designed to find a suitable design for the use of that function.
Keywords: Icon; Confusion; Affordance; Color perception and design